Puppets, kites and the swirling waters: Convergent boundaries in a site-specific performance. Issue 2 (1st December 2017) - Listengarten, Julia; Yates, Sarah
As a group of theatre makers in the School of Performing Arts at the University of Central Florida, we conceived a site-specific performance on university campus that involved both traditional and non-traditional production layers. The live symphony concert – an annual event with pre-established history and audience-base – evolved in a visual performance which included a site-specific dance in combination with performance objects such as kites and puppets. This project served as a 'practice as research' investigation of convergent boundaries between artistic hierarchies in a creative process and explored the ways in which multiple layers of a site-specific event intermingle, manipulate, repel and consume one another.